2023
DOI: 10.3390/ani13091531
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Mannheimia haemolytica-Specific IgG, IgM and IgA in Sera and Their Relationship to Respiratory Disease in Cattle

Korakrit Poonsuk,
Carita Kordik,
Matthew Hille
et al.

Abstract: Mannheimia haemolytica is one of the major causes of bovine respiratory disease in cattle. The organism is the primary bacterium isolated from calves and young cattle affected with enzootic pneumonia. Novel indirect ELISAs were developed and evaluated to enable quantification of antibody responses to whole cell antigens using M. haemolytica A1 strain P1148. In this study, the ELISAs were initially developed using sera from both M. haemolytica-culture-free and clinically infected cattle, then the final prototyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…Low body weight can also be affected by diseases other than feed and management. Previous research generally found enzootic pneumonia in calves and young cattle (Poonsuk et al, 2023). Diseases can also reduce production, one of which is bovine interdigital phlegmon (IP), an infective bacterial disease due to lesions in the interdigital skin (Celani et al, 2023).…”
Section: Advances In Animal and Veterinary Sciencesmentioning
confidence: 99%
“…Low body weight can also be affected by diseases other than feed and management. Previous research generally found enzootic pneumonia in calves and young cattle (Poonsuk et al, 2023). Diseases can also reduce production, one of which is bovine interdigital phlegmon (IP), an infective bacterial disease due to lesions in the interdigital skin (Celani et al, 2023).…”
Section: Advances In Animal and Veterinary Sciencesmentioning
confidence: 99%